Young American Muslims : dynamics of identity - Kabir, Nahid Afrose (Edinburgh : Edinburgh University Press, 2014)
"This book presents a journey into the ideas, outlooks and identity of young Muslims in America today. Based on around 400 in-depth interviews with young Muslims from Florida, Maryland, Massachusetts, Michigan, New York and Virginia, all the richness and nuance of these minority voices can be heard. Many young Americans cherish an American dream, 'that all men are created equal'. And the election of America's first black President in 2008 has shown that America has moved forward. Yet since 9/11 Muslim Americans have faced renewed challenges, with their loyalty and sense of belonging being questioned."--Publisher's website.
Introduction : my journey and the 'Muslim question' -- Identity matters -- The culture debate -- What does it take to be an American? -- Reflections on the American media -- Barack Hussein Obama and young Muslims' political awareness -- The Palestinian question -- From here to where?
ENH
Keywords: Muslims -- United States -- Ethnic identity; Muslim youth -- United States -- Ethnic identity; Muslims -- United States -- Attitudes; Muslim youth -- United States -- Attitudes